PENGARUH TOTAL QUALITY MANAGEMENT (TQM) TERHADAP KINERJA KARYAWAN DENGAN SISTEM PENGHARGAAN (REWARD) SEBAGAI VARIABEL MODERATING PADA PT. TELKOM INDONESIA WITEL RIAU DARATAN DI KOTA PEKANBARU - Muslih Fadhilah; Restu Restu; Siregar Andreas Prima (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2022)
The current rapid growth of the world economy has reached a situation wherecompetition has become a problem that must be faced by business people in everyeconomic sector. PT. Telkom Indonesia Witel Riau Daratan is a company engagedin the field of information and communication as well as the provision of completetelecommunications services and networks in Indonesia. Employees at PT. TelkomIndonesia Witel Riau Daratan must give its best performance. Total QualityManagement and reward systems are things that must be considered by companyleaders in order to improve employee performance at PT. Telkom Indonesia WitelRiau Daratan. This study aims to determine the effect of Total Quality Management(TQM) on employee performance with a reward system as a moderating variablefor employees at PT. Telkom Indonesia Witel Riau Mainland. Primary data werecollected with a questionnaire as an instrument. To test the hypothesis of the use ofSEM with the SmartPLS application assistance program. The population in thisstudy includes employees at the manager level and assistant managers. Thesampling technique used the census method, the sample of this study found 33employees. The results of the study indicate that: 1) there is a significant effect ofTotal Quality Management (TQM) on employee performance at PT. TelkomIndonesia Witel Riau Daratan in Pekanbaru City, 2) there is a significantinteraction effect between Total Quality Management (TQM) and the rewardsystem (Reward) on employee performance and the reward system is a moderatingvariable at PT. Telkom Indonesia Witel Riau Daratan in Pekanbaru City. Keywords: Total Quality Management (TQM), Reward System, EmployeePerformance.